Ssn6-Tup1 global transcriptional co-repressor: Role of the N-terminal glutamine-rich region of Ssn6 - Tartas, Athanassios (PLoS One, 2017)
The Ssn6-Tup1 complex is a general transcriptional co-repressor formed by the interaction of Ssn6, a tetratricopeptide repeat (TPR) protein, with the Tup1 repressor. We have previously shown that the N-terminal domain of Ssn6 comprising TPRs 1 to 3 is necessary and sufficient for this interaction and that TPR1 plays critical role. In a subsequent study, we provided evidence that in the absence of Tup1, TPR1 is susceptible to proteolysis and that conformational change(s) accompany the Ssn6-Tup1 complex formation. In this study, we address the question whether the N-terminal non-TPR, glutamine-rich tail of Ssn6 (NTpolyQ), plays any role in the Ssn6/Tup1 association. Our biochemical and yeast-two-hybrid data show that truncation/deletion of the NTpolyQ domain of Ssn6 results in its self association and prevents Tup1 interaction. These results combined with in silico modeling data imply a major role of the NTpolyQ tail of Ssn6 in regulating its interaction with Tup1.